Facing Climate Change in the LDCs: How to Implement the Istanbul Programme of Action - Patrick Guillaumont; Catherine Simonet (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
The climate change issue is briefly considered in the chapter 4 "Priority areas for actions", section F «Multiple crises and other emerging challenges» of the Istanbul Declaration. In this section, climate change is examined with environmental sustainability and besides economic shocks and disaster risk reduction. The monitoring of this section about climate change is fairly complex, since the related actions to be taken do not refer to monitoring indicators, measurable and observable. In order to monitor these actions we propose to first identify through an indicator of physical vulnerability to climate change the level and type of vulnerability to climate change of the LDCs. Then, we evaluate two types of actions recommended by the IPoA: establishment of NAPAs and the LDC Fund orientation. The first part of the paper evidences the high level of vulnerability of the LDCs and heterogeneous profiles of vulnerability to climate change among them. The second part is an assessment of the actions recommended by the IPoA for the adaptation to climate change considering the need of the countries as identified by the index.Revised version May 2014.
Keywords: Q54; Q56; 330